Tensile properties and morphology of dynamic vulcanized ENR-5/EVA blends : different vulcanization system - Mohamad, Z.; Ismail, H.; Thevy, R. Chantara (Faculty of Chemical Engineering & Natural Resources, 2008)

(untitled)
Blends of epoxidized natural rubber (ENR-50) and ethylene vinyl acetate (EVA), with varying proportion of the components, were dynamically vulcanized using different crosslinking systems, namely, sulfur and dicumyl peroxide (DCP). The blends were prepared by melt mixing in Haake Rheometer. The effect of curing systems on the tensile properties and morphology were investigated. The results revealed that, dynamic vulcanization are capable to improve tensile properties of ENR-50/EVA blends by producing a finer and homogenous dispersed phase of ENR-50 in EVA matrix. Dispersed phase is in a form of crosslink rubber particles (ENR-50) which have the ability to improve tensile properties of the blend. Overall morphology showed that, crosslink phase will become a dispersed phase at all blend ratios.